2012
DOI: 10.1097/ccm.0b013e318258ff01
|View full text |Cite
|
Sign up to set email alerts
|

Fluid overload and fluid removal in pediatric patients on extracorporeal membrane oxygenation requiring continuous renal replacement therapy*

Abstract: Objective In pediatric patients fluid overload (FO) at continuous renal replacement (CRRT) initiation is associated with increased mortality. The aim of this study was to characterize the association between fluid overload at CRRT initiation, fluid removal during CRRT, the kinetics of fluid removal and mortality in a large pediatric population receiving CRRT while on extracorporeal membrane oxygenation (ECMO). Design Retrospective chart review. Setting Tertiary children’s hospital Patients ECMO patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
134
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 26 publications
11
134
1
2
Order By: Relevance
“…Future work should aim to determine a mechanism for this finding. Fluid overload is associated with mortality in pediatric patients requiring CRRT [23][24][25][26][27] ; however, no study to date has demonstrated causality. Selewski et al 27 demonstrated in We did not consider hospital LOS, post-ECLS-days, or total mechanical ventilation-days in the multiple regression models, as these are in the direct pathway from exposure to outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should aim to determine a mechanism for this finding. Fluid overload is associated with mortality in pediatric patients requiring CRRT [23][24][25][26][27] ; however, no study to date has demonstrated causality. Selewski et al 27 demonstrated in We did not consider hospital LOS, post-ECLS-days, or total mechanical ventilation-days in the multiple regression models, as these are in the direct pathway from exposure to outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have suggested the importance of initiating CRRT during ECMO in patients in the early phases of renal dysfunction with fluid overload or inflammation [23]. In addition, Selewski et al [24] reported that initiating CRRT before the development of a significant fluid overload may be more clinically effective than attempting fluid removal after the fluid overload has developed. Thus, the lack of a survival benefit with early dialysis in our study may be an indicator of the fact that CRRT had not been initiated early enough in our ECMO patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the application of ECMO may cause deterioration in renal functions and acute renal injuries that can lead to increase in mortality rates (23)(24)(25). Nephrotoxic agents used in the patients treated with ECMO lead to decreased renal perfusion during ECMO support and infections, blood transfusions, systemic inflammatory reaction syndrome and hemolysis may be associated with renal damage.…”
Section: Discussionmentioning
confidence: 99%